Ahmed Versus Baerveldt Glaucoma Drainage Implantation in Patients With Markedly Elevated Intraocular Pressure (≥30 mm Hg). Issue 9 (September 2016) - Resende, Arthur F.; Moster, Marlene R.; Patel, Neal S.; Lee, Daniel; Dhami, Hermandeep; Pro, Michael J.; Waisbourd, Michael
Abstract : Purpose: Glaucoma patients with markedly elevated intraocular pressure (IOP) are at risk for developing severe hypotony-related complications. The goal of this study was to compare the surgical outcomes of the Ahmed Glaucoma Valve (AGV) and the Baerveldt Glaucoma Implant (BGI) in this patient population. Methods: Patients with preoperative IOP≥30 mm Hg were included. Outcome measures were: (1) surgical failure (IOP>21 mm Hg or <30% reduction from baseline or IOP⩽5 mm Hg on 2 consecutive follow-up visits after 3 mo, or additional glaucoma surgery, or loss of light perception) and (2) surgical complications. Results: A total of 75 patients were included: 37 in the AGV group and 38 in the BGI group. The mean±SD follow-up was 2.3±1.6 years for the AGV group and 2.4±1.7 years for the BGI group ( P =0.643). Mean preoperative IOP was 38.7±6.5 mm Hg for the AGV group and 40.8±7.6 mm Hg for the BGI group. At the last follow-up, 10 (27.0%) patients failed in the AGV group compared with 6 (15.8%) patients in the BGI group ( P =0.379). The BGI group had higher rate of flat or shallow anterior chamber (n=4, 10%) compared with the AGV group (n=0, 0%) ( P =0.043). Conclusions: Failure rates of AGV and BGI in patients with IOP≥30 mm Hg were comparable. There were more early hypotony-related complications in the BGI group; however, none were vision threatening. Both glaucoma drainage implants were effective in treating patients with uncontrolled glaucoma in an emergency setting.